Influence of PRRSV-1 vaccination and infection on mononuclear immune cells at the maternal-fetal interface - Stas, Melissa R.; Kreutzmann, Heinrich; Stadler, Julia; Sassu, Elena L.; Mair, Kerstin H.; Koch, Michaela; Knecht, Christian; Stadler, Maria; Dolezal, Marlies; Balka, Gyula; Zaruba, Marianne; Mötz, Marlene; et al. (Frontiers in Immunology, 2022)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most devastating viruses for the global swine industry. Infection during late gestation causes reproductive failure but the local immune response in utero remains poorly understood. In this study, an experimental PRRSV-infection model with two different PRRSV-1 field isolates was used to investigate the immune cell phenotypes at the maternal-fetal interface during late gestation. In addition, phenotypic changes induced by a modified live virus (MLV, ReproCyc® PRRS EU) vaccine were studied. Vaccinated (n = 12) and non-vaccinated pregnant gilts (n = 12) were challenged with either one of the PRRSV-1 field isolates (low vs. high virulent, LV or HV) or sham-inoculated at day 84 of gestation. Twenty-one days post infection all gilts were euthanized and the fetal preservation status for all fetuses per litter was assessed. Leukocytes from the maternal-fetal interface were isolated and PRRSV-induced changes were investigated using ex vivo phenotyping by flow cytometry. PRRSV load in tissue from the maternal endometrium (ME) and fetal placenta (FP) was determined by RT-qPCR. In the ME, a vast increase in CD8β T cells with CD8αposCD27dim early effector phenotype was found for fetuses from the non-vaccinated LV and HV-challenged gilts, compared to non-treated and vaccinated-only controls. HV-challenged fetuses also showed significant increases of lymphocytes with effector phenotypes in the FP, including NKp46pos NK cells, CD8αhigh γδ T cells, as well as CD8αposCD27pos/dim CD4 and CD8 T cells. In vaccinated animals, this common activation of effector phenotypes was more confined and the fetal preservation status significantly improved. Furthermore, a negative correlation between the viral load and CD163highCD169pos mononuclear phagocytic cells was observed in the FP of HV-infected animals. These results suggest that the strong expansion of effector lymphocytes in gilts that were only infected causes immune-pathogenesis rather than protection. In contrast, the attenuated MLV seems to dampen this effect, yet presumably induces memory cells that limit reproductive failure. This work provides valuable insights into changes of local immune cell phenotypes following PRRSV vaccination and infection.